Measuring present runoff erosion - Figueiredo, Tomás de (2014)
Soil erosion by water or, with a narrower focus, runoff erosion, address natural phenomena that integrate and combine in a sometimes rather complex way several physical processes, involving energy and mass transfer from the atmosphere to surface ground and along the actual gradients over ground surface. This in turn, is reflected in the assessment complexity and on that of the interpretation of assessment results. In order to mitigate such difficulties and constraints, it is important to clearly identify the object under assessment. However, this is not a simple matter as time and spatial scales very much affect erosional processes occurrence and rates. In fact, erosion is a spatially distributed phenomenon, involving sediment transfer along hill-slopes and from slope plans to the linear structures of the natural drainage network. As well, erosion is a time discontinuous, episodic, phenomenon, following the lack in time continuity of the erosive agent, the rainfall. Moreover, erosion phenomena combine continuous and threshold type of mechanisms, meaning that erosional responses may vary from nil to very high magnitude. This range is determined by changes in erosion processes contribution to total loss, from splash everywhere in a field or catchment in virtually all rainfalls (negligible to low loss), to interrill erosion in some events with Hortonian overland flow generation (low to severe loss), to gully incision in very few heavy and prolonged rainfall episodes, with topographically concentrated overland flow running over saturated soil (severe to very severe loss). Assessing runoff erosion encompasses these wide ranges of processes time and space occurrence and continuity. Therefore, no such thing as a normalized rosion measurement methodology exists, and a wide set of methods historically eveloped, according to research needs and progresses in specific technology and instrumentation. General classification of methods to assess runoff erosion requires definition of the consistently applicable criteria, coupled with the practical goal of reaching easy application. The proposed categories are designed to meet those requirements. For each section the layout is: comprehensive list of methods or types of methods and for each of these, scope, description, discussion with application conditions, pros and cons.